Non-Optic Glioma-like Lesions in Adult Neurofibromatosis Type 1 Patients - Walter Taal; Bart Zick; Bart J. Emmer; Martin J. van den Bent (Diagnostics)
Background/Objectives: Physicians face clinical dilemmas in the diagnosis of non-optic intraparenchymal lesions on MRI brain scans of patients with neurofibromatosis type 1. As the incidence and evolution of these lesions into adulthood remain unclear, we conducted a retrospective study on this topic. Methods: All adult neurofibromatosis type 1 patients who had at least one MRI brain scan in our center were selected for this study. Brain lesions with contrast enhancement after gadolinium administration and/or mass effect were named “glioma-like lesions”. Results: In our cohort of 396 adult neurofibromatosis type 1 patients, 182 had at least one MRI scan of the brain. A total of 48 glioma-like lesions were found in 38/182 patients. The majority of glioma-like lesions remained stable, decreased in size or even disappeared during a median follow-up time of 8.5 years. Twelve glioma-like lesions in 11/182 patients were resected or biopsied, and histology showed gliomas of astrocytic origin (WHO grade 1–4). Conclusions: It was concluded from these data that asymptomatic glioma-like lesions on MRI brain scans in neurofibromatosis type 1 patients, either with contrast enhancement and/or mass effect, had an indolent nature. Mildly symptomatic or asymptomatic patients can therefore be followed without invasive diagnostic and therapeutic procedures.